Processing of flour from sweet potato (Ipomoea batatas, Linn. Var. Batanes) - Lizada, Ma. Luz C.
ABSTRACT Two local varieties os sweet potato -- the Batanes and BNAS -- were compared for suitability for flour processing. The Batanes variety had a specific gravity of 1.25, 34.2 % dry matter and 2.62% starch which make it more suitable for processing than the BNAS variety since these values were all higher for the Batanes variety compared to the BNAS. The former has, however, a lower calcium content, 105mg/100g. and a higher content of reducing sugars, 0.70% (w/w). than the latter variety. Prior to processing into flour, the time for dehydration of the sweet potato slices was determined. It was found that 140-180 minutes of dehydration in a forced draft cabinet drier at a temperature range of approximately 60-70°C is adequate. The processed flour had a final moisture content of 6.6%, a pH of 3.8 and absorption property of 66.3%. By subjective evaluation, the flour was described as creamy off-white, with a fine texture, a pleasant odor and uniform overall general appearance. The acceptable level of sweet potato flour in noodles as determined and results showed that samples with 0% (control pure wheat flour), 10% and 20% sweet potato flour exhibited no significant from each other.